The Influence of Halal Knowledge and Labeling on Food Product Purchase Decisions - Febrilyantri, Candra (Institut Agama Islam Negeri Ponorogo, 2022)
The food and beverage industry is currently more concerned about the manufacture and procurement of halal food products because the level of public knowledge is increasing with social media and is supported by data on the development of Muslims worldwide. For Muslims, the essential thing to do when buying products is halalness. This study examines the level of knowledge and halal labeling on purchase decisions of food products for IAIN Ponorogo students. The number of samples in this study was 100 people, with multiple linear regression analysis methods and using the SPSS for Windows v25. Based on the result of the SPSS test, the result was: (i) Based on the simulation test, knowledge variables and halal labeling affected food purchasing decisions. (ii) Based on a partial test, the knowledge variable does not affect food purchasing decisions, but the halal labeling variable affects food purchasing decisions.